Reducing Boredom Using Scent to Improve Constructs Critical to Learning. (September 2014) - Jones, David L.; Dechmerowski, Sara; Oden, Razia; Pike, William
Boredom is an emotion that can have negative consequences in learning environments. Odor research has demonstrated that scents elicit strong emotional responses during exposure; however, there is limited research on how to leverage odors to reduce boredom. The present study examined the impact of four ambient odors (peppermint, cinnamon, lavender, and urine) on boredom, motivation, and engagement. Results revealed that cinnamon significantly reduced feelings of boredom; however, peppermint, lavender, and urine did not significantly impact boredom. Results also demonstrated that the presence of boredom significantly decreased motivation and engagement. These findings indicate that boredom is an important connection between odors and their effect on constructs critical to learning. The results of this study can be applied to educational settings, workplaces, and other boredom-prone settings.